Functional mosaicism of membrane proteins in vesicles of Escherichia coli. - Adler, L W (1977)
Membrane vesicles of Escherichia coli prepared by osmotic lysis of lysozyme ethylenediaminetetracetate (EDTA) spheroplasts have approximately 60% of the total membrane-bound reduced nicotinamide adenine dinucleotide (NADH) dehydrogenase (ED 1.6.99.3) and Mg2+-adenosine triphosphatase (ATPase) (EC 3.6.1.3) activities exposed on the outer surface of the inner membrane. Absorption of these vesicles with antiserum prepared against the purified soluble Mg2+-ATPase resulted in agglutination of approximately 95% of the inner membrane vesicles, as determined by dehydrogenase activity, and about 50% of the total membrane protein. The unagglutinated vesicles lacked all dehydrogenase activity and may consist of outer membrane. Lysozyme-EDTA vesicles actively transported calcium ion, using either NADH or adenosine 5'-triphosphate (ATP) as energy source. However, neither D-lactate nor reduced phenazine methosulfate energized calcium uptake, suggesting that the observed calcium uptake was not due to a small population of everted vesicles. Transport of calcium driven by either NADH or ATP was inhibited by simultaneous addition of D-lactate or reduced phenazine methosulfate. Proline transport driven by D-lactate oxidation was inhibited by either NADH oxidation or ATP hydrolysis. These results suggest that the portion of the total population of vesicles capable of active transport, i.e., the inner membrane vesicles, are functionally a homogeneous population but cannot be categorized as either right-side-out or everted, since activities normally associated with only one side of the inner membrane can be found on both sides of the membrane of these vesicles. Moreover, the data indicate that oxidation of NADH or hydrolysis of ATP by externally localized NADH dehydrogenase or Mg2+-ATPase establishes a protonmotive force of the opposite polarity from that established through D-lactate oxidation.